miRNA-driven sensitization of breast cancer cells to Doxorubicin treatment following exposure to low dose of Zinc Oxide nanoparticles - Ali A. Alshamrani; Sami B. Bin Salman; Nasser B. Alsaleh; Mohammed A. Assiri; Mohammed M. Almutairi; Sultan Almudimeegh; Abdulrahman Alwhaibi; Homood M. As Sobeai (Elsevier, 2024)
The impact of Engineered nanomaterials (ENMs) (i.e., Zinc Oxide nanoparticles (ZnO NPs)) on human health has been investigated at high and unrealistic exposure levels, overlooking the potential indirect harm of subtoxic and long exposures. Therefore, this study aimed to investigate the impacts of subtoxic concentrations of zinc oxide (ZnO NPs) on breast cancer cells' response to Doxorubicin. Zinc oxide nanoparticles caused a concentration-dependent reduction of cell viability in multiple breast cancer cell lines. A subtoxic concentration of 1.56 µg/mL (i.e., no observed adverse effect level) was used in subsequent mechanistic studies. Molecularly, miRNA profiling revealed significant downregulation of 13 oncogenic miRNAs (OncomiRs) in cells exposed to the sub-toxic dose of ZnO NPs followed by doxorubicin treatment. Our comprehensive bioinformatic analysis has identified 617 target genes enriched in ten pathways, mainly regulating gene expression and transcription, cell cycle, and apoptotic cell death. Several tumor suppressor genes emerged as validated direct targets of the 13 OncomiRs, including TFDP2, YWHAG, SMAD2, SMAD4, CDKN1A, CDKN1B, BCL2L11, and TGIF2. This study insinuates the importance of miRNAs in regulating the responsiveness of cancer cells to chemotherapy. Our findings further indicate that being exposed to environmental ENMs, even at levels below toxicity, might still modulate cancer cells' response to chemotherapy, which highlights the need to reestablish endpoints of ENM exposure and toxicity in cancer patients receiving chemotherapeutics.